2023
DOI: 10.1039/d3tc00861d
|View full text |Cite
|
Sign up to set email alerts
|

Topological defects stabilized by a soft twist-bend dimer and quantum dots lead to a wide thermal range and ultra-fast electro-optic response in a liquid crystalline amorphous blue phase

Abstract: Amorphous Blue phase, or BPIII, a mesophase exhibited by highly chiral liquid crystals, is increasingly being investigated for next-generation displays due to its attractive electro-optical properties such as sub-millisecond response...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 61 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…The NPs of such dimensions, when doped in the BP, are known to get trapped inside the cores of disclination lines. 41–44 Therefore, for the Se–BP ( i.e. , the nanoparticle-doped BPI), the n DTC and n Disclination are considered to be 1.6 and 3.07, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPs of such dimensions, when doped in the BP, are known to get trapped inside the cores of disclination lines. 41–44 Therefore, for the Se–BP ( i.e. , the nanoparticle-doped BPI), the n DTC and n Disclination are considered to be 1.6 and 3.07, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The disclination cores of BP are known to act as trapping sites for dopants such as nanoparticles, polymers, etc . 41–44 Therefore the as-synthesized Se NPs (∼5 nm dia) can be confined efficiently inside the disclination cores of BPI, forming a stable cubic lattice.…”
Section: Resultsmentioning
confidence: 99%
“…The chiral dopant is added to induce chirality to the medium and hence the BPI. The LC dimer, which exhibits the twist bend nematic phase (NTB) with ultralow bend elastic constant and saddle-splay deformation, is added to increase the thermal range of BPI. , Rhodamine B (from TCI Chemicals ), which possesses a high quantum yield of 90% and exhibits an emission wavelength (570 nm) in the vicinity of the PBG of BP, is chosen as the dye material for the PL study. Se NPs (diameter ∼5 nm), the high-index particles of choice, capped with polyvinylpyrrolidone (PVP) (to facilitate uniform dispersion of NPs in the BPLC medium), are synthesized in the laboratory using the modified chemical reduction method, as reported in our previous publication .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Cordoyiannis et al demonstrated that quantum dots essentially stabilize BPIII [ 67 ]. Khatun and Nari et al reported stabilizing BPIII by using a twist–bend nematic LC and surface-functionalized quantum dots (QDs: CdSe (core)/ZnS (shell) tethered with octadecylamine) [ 68 ]. Adding a twist–bend nematic dimer N TB LC ( Figure 22 ) to a mixture comprising a nematic liquid crystal mixture and a chiral dopant S-811 stabilizes the cubic BPI, as shown in Figure 23 a.…”
Section: Materials Stabilizing Bpiiimentioning
confidence: 99%
“…Electro-optical switching in BPIII by using polymer-stabilized materials [ 14 , 49 , 75 , 76 ] or a low-molecular-mass system [ 68 , 77 ] has been reported. Gandhi and Chien et al reported that a polymer network based on BPIII can memorize the 3D structure on the original PS-BPIII from which they are nanoengineered, and can transfer this structural information to achiral nematic LCs [ 49 ].…”
Section: Physical Properties In Bpiiimentioning
confidence: 99%